Composite material electronic aluminum foil and manufacturing method thereof

By adopting the three-layer composite structure electronic aluminum foil design, the thickness and element content of the core layer and the erosion layer are optimized, and the problem of inconsistent holes after corrosion of electronic aluminum foil in the prior art is solved, and the improvement of high bending, high capacity and mechanical properties is achieved, and the generation of interlayers is avoided.

CN119905354APending Publication Date: 2025-04-29URUMQI ZHONGRONG ELECTRONIC MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311406872.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

After corrosion, the lengths of the corrosion holes of the existing electronic aluminum foil are different, which makes it difficult for the mechanical properties and capacitance of the anode aluminum foil to reach the optimal level at the same time, and there is a problem of interlayer generation.

Method used

The electronic aluminum foil design is adopted with a three-layer composite structure, with the intermediate layer being a core layer that controls mechanical properties, and the upper and lower layers being an erosion layer that facilitates the growth of tunnel holes. By optimizing the cubic texture and chemical composition of the aluminum foil, the thickness and element content of the core layer and erosion layer are controlled to ensure the consistency of the holes after corrosion and the mechanical properties of the product.

Benefits of technology

The electronic aluminum foil has a higher consistency in tunnel holes after corrosion, and the high bending, high capacity and mechanical properties of the anode foil are improved, which avoids the generation of interlayers and improves the overall performance of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004516838350000141
    Figure BDA0004516838350000141
  • Figure HDA0004516838360000011
    Figure HDA0004516838360000011
  • Figure HDA0004516838360000012
    Figure HDA0004516838360000012
Patent Text Reader

Abstract

The invention discloses a composite material electronic aluminum foil and a manufacturing method thereof, and belongs to the technical field of electronic aluminum foil manufacturing. In order to increase the consistency of the hole-forming length of the anode aluminum foil of the aluminum electrolytic capacitor and improve the mechanical property and the capacitance of the anode aluminum foil, a high-purity aluminum core layer is prepared on a plate ingot by adopting a core layer plate ingot casting technology and a special ingot casting method in the production process of electronic aluminum foil, and the high-purity aluminum core layer is obtained through multiple rolling procedures. The novel composite electronic aluminum foil containing the high-purity aluminum core layer with a certain thickness is prepared, and the high-purity aluminum core layer can prevent the growth of tunnel holes, so that the consistency of corrosion hole generation is improved, the uniformity of the hole generation length of the corrosion aluminum foil is increased, and the product capacity and mechanical performance are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electronic aluminum foil manufacturing, and in particular to a composite material electronic aluminum foil and a manufacturing method thereof. Background Art

[0002] Anode aluminum foil for electrolytic capacitors is the main component for producing capacitors, and the performance of its products directly determines the grade of aluminum electrolytic capacitors. With the development of miniaturization of aluminum electrolytic capacitors, anode aluminum foil for electrolytic capacitors is also required to have high capacity and high bending performance after corrosion. With the rapid development of electronic technology, the use of aluminum electrolytic capacitors has become more extensive, and it has also been widely used in environmental protection and energy-saving fields such as rail transportation, flat panel displays, solar energy, wind power batteries, etc., which has promoted the development of electronic aluminum foil more rapidly.

[0003] The capacitance of electrolytic capacitors is the most important indicator of their performance. Currently, corrosion technology is mostly used to make the surface of aluminum foil undulate in order to expand the surface area of ​​the plate and greatly increase the specific capacitance. At the same time, linkage production is adopted in the manufacturing process of aluminum electrolytic capacitors, and it is necessary to ensure that the anode aluminum foil meets certain mechanical performance indicators.

[0004] The current production process of high-voltage anode aluminum foil is: ingot (consistent composition) - soaking - hot rolling - cold rolling - annealing - finished product. The ingot for high-voltage anode aluminum foil is the raw material for producing electronic aluminum foil for high-performance aluminum electrolytic capacitors. At present, the raw materials for producing high-voltage anode foil ingots are mainly three-layer refined aluminum and segregation refined aluminum in a certain proportion; by adding metal ingots and aluminum alloys, the content of some trace elements is increased. The control of trace elements in raw materials, the proportion of three-layer method and segregation method, and the control of element content in the final product are the prerequisites for ensuring the production quality of high-voltage anode foil ingots. At present, due to the limitations of various production processes, the grain distribution of high-voltage anode foil ingots prepared by the above two raw materials is uneven, which will have adverse effects on subsequent soaking, hot rolling, cold rolling, annealing and corrosion formation processes.

[0005] The current electronic aluminum foil is made of the same material and is integrally formed. After corrosion, the order of the holes formed is different, resulting in tunnel holes of different lengths. Some tunnel holes are long and some are short. After corrosion, holes are formed on the upper and lower surfaces of the aluminum foil to increase the surface area, which is called the erosion layer; the middle part is the remaining part after corrosion, which is called the core layer. The core layer ensures the strength and mechanical properties of the aluminum foil. In order to increase the capacitance, electrochemical corrosion or chemical corrosion is used to generate as many and longer corrosion tunnel holes as possible with effective apertures on the upper and lower surfaces of the aluminum foil to increase its surface area. In order to ensure the strength of the anode aluminum foil, a certain thickness of the core layer must be maintained. The thickness of the aluminum foil core layer and its degree of corrosion are difficult to control well. In particular, when the upper and lower surfaces of the entire electronic aluminum foil are corroded, there are differences in local corrosion properties, resulting in some deep corrosion holes and some shallow corrosion holes. When the deep hole has penetrated the middle part, the corrosion depth of the shallow hole is still very small (Figure 1 ), which cannot guarantee the strength of the electronic aluminum foil, and it is difficult to achieve the best corrosion effect (ensuring that the mechanical properties meet the standards and achieve the highest capacity corrosion). Moreover, the probability of the product not meeting the mechanical properties standards is greater, resulting in a higher number of unqualified products.

[0006] At present, the anode aluminum foil of electrolytic capacitors produced domestically cannot meet the performance requirements of high capacity and high bending in the market, especially in the Japanese high-end corrosion foil market, which mainly uses anode aluminum foil for high-voltage electrolytic capacitors produced in Japan.

[0007] With the rapid development of the electronics industry and the information industry, electrical products and information technology equipment are constantly developing towards high performance, miniaturization, and integration, and aluminum electrolytic capacitors are indispensable components in modern electrical products and information technology equipment. To a large extent, the unit volume capacitance of aluminum electrolytic capacitors depends to a large extent on the specific capacitance of the anode foil electrode. In order to meet the needs of miniaturization of electrolytic capacitors, improving the specific capacitance of the anode foil electrode is an important technical measure to adapt to the miniaturization of electrolytic capacitors and even the entire electrical equipment. According to the capacitance formula of parallel plate capacitors C = εS / d, it can be seen that the capacitor capacitance C is proportional to the surface area S and dielectric constant ε of the electrode, and inversely proportional to the distance between the plates. Therefore, when the material is determined, the dielectric constant ε is determined accordingly, and the electrode distance d should not be too small, otherwise the capacitor will be broken down. At this time, if you want to increase the capacitance, expanding the electrode surface area becomes the main factor. And the deployment of appropriate chemical composition and improving the cubic texture of the aluminum foil for the anode of the electrolytic capacitor is an important way to expand the surface area of ​​the electrode and thus increase the specific capacitance of the anode foil. Prior art "Invention name: A method for manufacturing aluminum foil for high-voltage anode of electrolytic capacitor, patent number CN1807673B" discloses a method for manufacturing aluminum foil for high-voltage anode of electrolytic capacitor, including melting and casting steps: (A) mixing auxiliary elements in high-purity aluminum liquid; (B) ingot homogenization annealing and hot rolling steps: (C) cold rolling step; (D) intermediate annealing step: an annealing treatment is performed before the last cold rolling step. This invention appropriately mixes the chemical composition of aluminum liquid, then ingot casting, homogenization annealing, hot rolling, cold rolling, and before the last cold rolling, an intermediate annealing is performed to obtain a hard aluminum foil for high-voltage anode. Its unique formula and manufacturing process can generate more corrosion cores on the aluminum foil, and at the same time can increase the content of {100} face cubic texture, so that the subsequent corrosion process can generate more corrosion holes and various corrosion tunnels in the {100} direction perpendicular to the foil surface, increase the surface area of ​​the aluminum foil, and then increase the specific capacitance of the anode foil; however, this method has insufficient control over the growth length of various corrosion tunnels generated in the {100} direction perpendicular to the foil surface, and the corrosion tunnel holes are long and short. Long holes reduce the mechanical properties of the product, and short holes reduce the capacity index of the product. Prior art "Invention name: A composite material electronic aluminum foil and its preparation method, patent number CN111195657B" discloses an electronic aluminum foil composite material and an electronic aluminum foil prepared therefrom, as well as a preparation method of the composite material electronic aluminum foil. This invention casts two kinds of plate ingots, and performs slagging, refining, degassing, standing, filtering, casting, double-sided milling, heating, hot rolling, surface cleaning (cleaning surface foreign matter), and then hot composite rolling, cold foil rolling and finishing, and the composite material electronic aluminum foil is obtained after finishing. This invention has a problem: after hot rolling, since aluminum is very easy to oxidize, there will be a layer of aluminum oxide film and residual rolling oil on the surface of the foil coil, which will generate an interlayer during the hot composite rolling process, and even local stratification will occur. Summary of the invention

[0008] The purpose of the present invention is to provide a composite electronic aluminum foil and a method for manufacturing the same, wherein the composite electronic aluminum foil can ensure both optimization of corrosion and strength and mechanical properties of the electronic aluminum foil itself, effectively resolving the contradiction between the increased specific capacitance of the electronic aluminum foil due to corrosion and the strength of the electronic aluminum foil itself in the prior art, and avoiding the problem of interlayer formation.

[0009] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0010] A composite electronic aluminum foil has a three-layer composite structure, wherein: the middle layer is a core layer for controlling mechanical properties, and the upper and lower layers are erosion layers that are beneficial to the growth of tunnel holes; the thickness of the electronic aluminum foil is 85 to 150 microns.

[0011] The core layer is a tunnel hole termination layer, in which the Al content is greater than 99.99wt.%; preferably, the chemical composition of the core layer is: Fe<10ppm, Si<15ppm, Cu<15ppm, Zn<2ppm, Ti<5ppm, Mn<5ppm, the total amount of other elements is <5ppm, and the balance is Al; the core layer thickness is 25 to 35 microns.

[0012] The erosion layer is a tunnel hole growth layer, and the Al content in the erosion layer is greater than 99.985wt.%; preferably, the chemical composition of the erosion layer is: Fe: 10-20ppm, Si: 5-30ppm, Cu: 50-60ppm, Zn<20ppm, Mg<5ppm, Ga<15ppm, Pb: 2-2.5ppm, and the remainder is Al; the thickness of the upper and lower erosion layers is kept consistent, and the thickness is controlled to be 30-60 microns.

[0013] The cubic texture of the electronic aluminum foil is 96-99%. After the corrosion treatment, the corrosion foil is bent 50-70 times, the tensile strength is 25Mpa-35Mpa, and the specific capacitance is 0.83μF / cm2-0.925μF / cm2.

[0014] The manufacturing method of the composite electronic aluminum foil comprises the following steps:

[0015] (1) Casting: Two kinds of high-purity aluminum liquid are prepared, and after smelting, heat preservation, refining and standing, semi-continuous casting is used to produce flat ingots. The casting temperature is 675-715°C, and the flat ingots are formed by rapid cooling. The two kinds of high-purity aluminum liquid are core layer aluminum liquid and erosion layer aluminum liquid;

[0016] (2) Homogenization: The formed flat ingot obtained in step (1) is homogenized in an annealing furnace at a temperature of 560 to 590° C. for a time of 16 to 24 hours, and then air-cooled to room temperature after homogenization;

[0017] (3) Hot rolling: The homogenized slab is hot rolled at a starting temperature of 500 to 550° C. and a final rolling temperature of 260 to 340° C. to obtain a hot rolled coil with a thickness of 5 to 9 mm;

[0018] (4) Cold rolling: cold rolling the hot rolled coil at a speed of 150 to 300 m / min to obtain a cold rolled coil with a thickness of 0.16 to 0.20 mm;

[0019] (5) Cleaning and intermediate annealing: The obtained cold-rolled coil is washed and scrubbed with deionized water containing alkaline additives in a cleaning device, and then rinsed with deionized water at a water temperature of 70-80°C. After cleaning, the cold-rolled coil is blown dry with high-pressure air and squeezed dry with a squeeze roller at the outlet; then intermediate annealing is performed in a continuous air cushion furnace at an annealing temperature of 310-345°C and an annealing speed of 22-36 m / min. After annealing, the coil is cooled to room temperature by air;

[0020] (6) Foil rolling: Foil rolling is used to apply a deformation of 8 to 48%, and the finished product is bright rolled with a reduction of ≤3% at a foil rolling speed of 160 to 310 m / min. The thickness of the finished product is 0.10 to 0.15 mm.

[0021] (7) Cleaning and finished product annealing: the cold-rolled coil obtained in step (6) is cleaned with deionized water containing an alkaline additive, and then rinsed with deionized water, the water temperature is controlled at 70-80° C., and the coil is dried by high-pressure air and squeezed with a squeeze roller at the outlet; during annealing, the coating is evenly sprayed onto the coil surface by spraying, and the aluminum foil finished product is annealed in a continuous air cushion furnace. After the finished product annealing, the electronic aluminum foil is obtained;

[0022] (8) Divide into rolls and pack.

[0023] In the above step (1), the chemical composition of the core layer aluminum liquid is controlled as follows: Fe<10ppm, Si<15ppm, Cu<15ppm, Zn<2ppm, Ti<5ppm, Mn<5ppm, other elements<5ppm, and the balance is Al;

[0024] In the above step (1), the chemical composition of the erosion layer aluminum liquid is controlled as follows: Fe: 10-20ppm, Si: 15-30ppm, Cu: 50-60ppm, Zn<20ppm, Mg<5ppm, Ga<15ppm, Pb: 2-2.5ppm, and the remainder is Al.

[0025] During the ingot preparation process of the above step (1), the aluminum liquid of the lower erosion layer-the aluminum liquid of the core layer-the aluminum liquid of the upper erosion layer are poured in sequence, and the thickness ratio is: the thickness of the upper and lower erosion layer aluminum ingots is kept consistent, the thickness of the upper erosion layer or the lower erosion layer accounts for 35.0-41.5% of the total thickness of the ingot, and the thickness of the core layer aluminum ingot is controlled to account for 17.0-30.0% of the total thickness of the ingot.

[0026] In the above step (7), annealing adopts multi-stage annealing at different temperatures, which are: first stage temperature 410-450°C, second stage temperature 550-590°C, third stage temperature 520-580°C, and the strip heat treatment speed is 25-38m / min.

[0027] In the above step (7), the coating is a suspension prepared by mixing zinc carbonate, manganese carbonate and calcium carbonate in any proportion and adding the mixture into water, the mass concentration is 0.001-0.005%, and the dosage is 2-5 L / min.

[0028] The design principle and beneficial effects of the present invention are as follows:

[0029] The present invention provides a method for preparing medium and high voltage electronic aluminum foil for high capacity and high strength capacitors. The preparation of the electronic aluminum foil includes: adopting a special ingot casting method to prepare a special flat ingot of electronic aluminum foil containing a certain thickness of corrosion-resistant material, and then preparing the electronic aluminum foil through various rolling processes. The new high-voltage aluminum electrolytic capacitor anode foil produced by the method has the characteristics of high bending, high capacity and higher consistency; this electronic aluminum foil is composed of a middle corrosion-resistant core layer and its upper and lower erosion layer materials. The middle core layer can avoid corrosion, avoid the formation of long tunnel holes, and ensure the mechanical properties of the anode aluminum foil. The upper and lower erosion layer materials provide the corrosion area of ​​the electronic aluminum foil to the greatest extent, solving the contradiction between the specific capacitance and its mechanical properties during the corrosion process of the electronic aluminum foil. It is suitable for use in an environment where the anode aluminum foil of the electrolytic capacitor cannot meet the high capacity and high bending requirements on the market. At the same time, the production method is simple, the process quality is easy to control, and the production method is suitable for mass production in large enterprises.

[0030] Compared with the prior art, the present invention has the following advantages:

[0031] 1. The method for preparing the medium- and high-voltage electronic aluminum foil for high-capacity and high-strength capacitors of the present invention: By adopting a cast corrosion-resistant core layer, the formation of excessively long corrosion holes can be effectively avoided, thereby controlling the mechanical properties of the anode foil product and greatly improving the capacity index of the product.

[0032] 2. The present invention optimizes the element ratio of the aluminum foil corrosion layer, which is beneficial to the formation of corrosion tunnel holes, thereby improving the capacity index of the anode foil product.

[0033] 3. The present invention can improve the mechanical indexes of anode foil products by adjusting the thickness of the aluminum foil core layer.

[0034] 4. The present invention avoids the formation of interlayers by adopting a special ingot casting method. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a cross-sectional diagram of aluminum foil corroded by the prior art; as can be seen from the figure, the corrosion tunnel holes of aluminum foil corroded by the prior art are of different lengths and have low consistency.

[0036] Figure 2 This is a cross-sectional view of the corroded aluminum foil of the present invention. DETAILED DESCRIPTION

[0037] In order to further understand the present invention, the present invention is described below in conjunction with examples, but the examples are only for further elaboration of the features and advantages of the present invention, rather than for limiting the claims of the present invention.

[0038] High-voltage aluminum foil belongs to the category of electronic aluminum foil. It is a corroded material that works under polar conditions. Electronic aluminum foils in different voltage ranges require different types of corrosion. Among them, high-voltage anode foil is generally a columnar tunnel-shaped corrosion structure. Because it needs a relatively thick oxide film that is resistant to high voltage when working under high voltage, but this thick oxide film cannot block the corrosion holes generated during corrosion production, otherwise it will cause the specific capacitance to decrease. In order to simultaneously meet the two conditions that high-voltage anode foil should have a thicker oxide film and a larger specific capacitance, columnar tunnel-shaped corrosion is the best choice. Therefore, the characteristics that aluminum foil materials should have include: (1) corrosion core; (2) corrosion channel; 3) corrosion channel length control. The corrosion core is a necessary condition to ensure that the material produces local microporous corrosion. It is an important measure to expand the surface area of ​​aluminum foil and thus improve the specific capacitance of the anode foil. The corrosion core, that is, the corrosion pore density, is mainly related to the chemical composition ratio and the existence of each impurity element. The corrosion channel allows the corrosive medium to diffuse inward, allowing the corrosion process to proceed smoothly. High-voltage anode foils at home and abroad generally use direct current electrochemical corrosion. Due to the {100} surface <001> The elastic modulus of the oriented surface is very small and the strength is the lowest, so under the action of direct current, corrosion occurs along the {100} plane. <001> Orientation-preferential corrosion expands to form square pits, and the effective area of ​​square holes is the largest, which is beneficial to expand the surface area of ​​aluminum foil, thereby increasing the specific capacitance of anode foil. The degree of development of cubic texture is mainly affected by process factors such as aluminum foil purity, hot rolling parameters, cold rolling parameters, and annealing. The length of the corrosion channel has a huge impact on the mechanical properties of the product. To ensure the mechanical performance indicators required for linkage production, the length of the tunnel hole must be controlled, that is, a certain thickness of uncorroded core layer must be retained.

[0039] In order to solve the above problems, the present invention provides a composite material electronic aluminum foil and a method for preparing the composite material electronic aluminum foil. The present invention adopts a special ingot casting method to prepare a special flat ingot for electronic aluminum foil containing a certain thickness of corrosion-resistant material, and then prepares the electronic aluminum foil through various rolling processes. This electronic aluminum foil is composed of a middle corrosion-resistant core layer and its upper and lower erosion layer materials. The middle core layer can avoid corrosion, avoid the formation of long tunnel holes, and ensure the mechanical properties of the anode aluminum foil. The upper and lower erosion layer materials provide the corrosion area of ​​the electronic aluminum foil to the greatest extent, solving the contradiction between the specific capacitance and its mechanical properties during the corrosion process of the electronic aluminum foil.

[0040] In the following examples, the deionized water containing the alkaline additive is a sodium dodecylbenzene sulfonate aqueous solution with a concentration of 0.5-2 wt.%; and the continuous air cushion furnace is a nitrogen protection annealing furnace.

[0041] Embodiment 1:

[0042] This embodiment provides a method for manufacturing a composite electronic aluminum foil, wherein the electronic aluminum foil is composed of an erosion layer on the upper and lower sides that is conducive to the growth of tunnel holes and a core layer that controls mechanical properties. For example, the thickness of the aluminum foil is controlled to be 125 to 127 microns.

[0043] The core layer contains Al>99.99wt.%, which is the tunnel hole termination layer. The content of each element in the core layer is as follows: Fe is 9ppm, Si=13ppm, Cu=14ppm, Zn=1.8ppm, Ti=2ppm, Mn<3ppm, other elements<5ppm, and the balance is Al; the thickness of the core layer is 25-28 microns

[0044] The erosion layer contains Al>99.985wt.%, which is the tunnel hole growth layer. The content of each element in the erosion layer is as follows: Fe: 18ppm, Si: 25ppm, Cu: 58ppm, Zn=18ppm, Mg=4ppm, Ga=12ppm, Pb: 2.1ppm, and the balance is Al; the thickness of the upper and lower erosion layers is consistent, and the thickness is controlled to be 49-51 microns

[0045] The preparation of the composite electronic aluminum foil of this embodiment includes the following steps:

[0046] Step 1) Casting: The raw materials for casting two kinds of high-purity aluminum liquid (core layer aluminum liquid and erosion layer aluminum liquid) are respectively smelted, heat-insulated, refined and left to stand, and then semi-continuously cast to produce ingots at a casting temperature of 705°C, and rapidly cooled to obtain formed ingots;

[0047] Step 2) homogenization: the formed flat ingot obtained in the previous step is homogenized in an annealing furnace at a homogenization temperature of 580° C. for 20 h, and then air-cooled to room temperature;

[0048] Step 3) hot rolling: hot rolling the flat ingot after the homogenization treatment in the previous step, with the hot rolling starting temperature of 520° C. and the final rolling temperature of 310° C. to obtain a hot rolled coil with a hot rolling thickness of 6 mm;

[0049] Step 4) cold rolling: cold rolling the hot rolled coil obtained in the previous step at a cold rolling speed of 280 m / min to obtain a cold rolled coil with an intermediate thickness of 0.17 mm;

[0050] Step 5) cleaning and intermediate annealing: the cold rolled coil obtained in the previous step is washed and scrubbed with deionized water containing alkaline additives, and then rinsed with deionized water, the water temperature is controlled at 73°C, the outlet is blown dry with high-pressure air and squeezed with a squeeze roller, and intermediate annealing is performed in a continuous air cushion furnace, the annealing temperature is 325°C, the annealing speed is 26m / min, and the coil is air-cooled to room temperature after annealing;

[0051] Step 6) Foil rolling: applying 38% deformation by foil rolling, the finished product pass adopts bright rolling with ≤3% reduction, the foil rolling speed is 270m / min, and the thickness of the obtained finished product is 0.14mm;

[0052] Step 7) cleaning and finished product annealing: the cold rolled coil obtained in the previous step is cleaned with deionized water containing an alkaline additive, and then rinsed with deionized water, the water temperature is controlled at 75°C, and the outlet is blown dry with high-pressure air and squeezed dry with a squeeze roller; during annealing, the coating is evenly sprayed on the coil surface by spraying, and the finished aluminum foil is annealed in a continuous air cushion furnace. The annealing adopts multi-stage annealing at different temperatures, the first stage temperature is 440°C, the time is 20min; the second stage temperature is 575°C, the time is 1.5h; the third stage temperature is 550°C, the time is 1h; the strip heat treatment speed is 32m / min; the coating is a suspension prepared by adding zinc carbonate, manganese carbonate and calcium carbonate to water after mixing in any proportion, the mass concentration is 0.004%, and the dosage is 3L / min.

[0053] Step 8) rolling and packaging; the obtained electronic aluminum foil has a cubic texture of 98%, and after corrosion treatment, the corrosion foil is bent 54 times, the tensile strength is 25Mpa, and the 520Vf specific capacitance is 0.86μF / cm2~0.88μF / cm2;

[0054] The high purity aluminum liquid composition described in step 1) is:

[0055] (1) Core aluminum liquid composition: Fe = 9ppm, Si = 13ppm, Cu = 14ppm, Zn = 1.8ppm, Ti = 2ppm, Mn < 3ppm, other elements < 5ppm, the balance is Al;

[0056] (2) Composition of molten aluminum in the corrosion layer: Fe: 18 ppm, Si: 25 ppm, Cu: 58 ppm, Zn: 18 ppm, Mg=4 ppm, Ga=12 ppm, Pb: 2.1 ppm, and the remainder is Al.

[0057] (3) Ingot casting: Cast in the order of (lower) erosion layer aluminum liquid - core layer aluminum liquid - (upper) erosion layer aluminum liquid. Thickness ratio: the thickness of the upper and lower erosion layer aluminum ingots is consistent, and the thickness ratio of each erosion layer is controlled to be 39.5%. The thickness control ratio of the core layer aluminum ingot is 21%.

[0058] Figure 2 This is a cross-sectional view of the corroded aluminum foil after the electronic aluminum foil of this embodiment has been corroded. Figure 2 It can be seen that the tunnel holes of the aluminum foil are more consistent after corrosion.

[0059] Embodiment 2:

[0060] The thickness of the composite electronic aluminum foil provided in this embodiment is controlled to be 145 to 147 microns.

[0061] The core layer has Al>99.99wt.%, which is the tunnel hole termination layer. The content of each element is as follows: Fe=8ppm, Si=12ppm, Cu=12ppm, Zn=1.6ppm, Ti=2ppm, Mn<2ppm, other elements<5ppm, and the balance is Al; the core layer thickness is 28-30 microns.

[0062] The erosion layer has Al>99.985wt.%, which is a tunnel hole growth layer. The content of each element is: Fe: 17ppm, Si: 24ppm, Cu: 56ppm, Zn 17ppm, Mg=3ppm, Ga=13ppm, Pb: 2.2ppm, and the remainder is Al; the thickness of the upper and lower erosion layers is kept consistent, and the thickness is controlled to be 58-59 microns.

[0063] The preparation of the composite electronic aluminum foil of this embodiment includes the following steps:

[0064] Step 1) Casting: The raw materials for casting two kinds of high-purity aluminum liquid (core layer aluminum liquid and erosion layer aluminum liquid) are respectively smelted, heat-insulated, refined and left to stand, and then semi-continuously cast to produce ingots at a casting temperature of 695° C. and rapidly cooled to obtain formed ingots;

[0065] Step 2) homogenization: the formed flat ingot obtained in the previous step is homogenized in an annealing furnace at a homogenization temperature of 560-590° C. for a homogenization time of 16-24 hours, and then air-cooled to room temperature;

[0066] Step 3) hot rolling: hot rolling the flat ingot after the homogenization treatment in the previous step, with the hot rolling start temperature of 535° C. and the final rolling temperature of 310° C. to obtain a hot rolled coil with a hot rolling thickness of 6 mm;

[0067] Step 4) cold rolling: cold rolling the hot rolled coil obtained in the previous step at a cold rolling speed of 270 m / min to obtain a cold rolled coil with an intermediate thickness of 0.18 mm;

[0068] Step 5) cleaning and intermediate annealing: the cold-rolled coil obtained in the previous step is washed and scrubbed with deionized water containing an alkaline additive, and then rinsed with deionized water, the water temperature is controlled at 75°C, the outlet is blown dry with high-pressure air and squeezed dry with a squeeze roller, and intermediate annealing is performed in a continuous air cushion furnace using a belt type, the annealing temperature is 325°C, the annealing speed is 25m / min, and the coil is air-cooled to room temperature after annealing;

[0069] Step 6) Foil rolling: applying 35% deformation through foil rolling, the finished product pass adopts bright rolling with a reduction of ≤3%, the foil rolling speed is 270m / min, and the thickness of the obtained finished product is 0.14mm;

[0070] Step 7) cleaning and finished product annealing: the cold-rolled coil obtained in the previous step is cleaned with deionized water containing an alkaline additive and then rinsed with deionized water, the water temperature is controlled at 75°C, and the outlet is blown dry with high-pressure air and squeezed dry with a squeeze roller; during annealing, the coating is evenly sprayed on the coil surface by spraying, and the finished aluminum foil is annealed in a continuous air cushion furnace. The annealing adopts multi-stage annealing at different temperatures, the first stage temperature is 435°C, the time is 20min; the second stage temperature is 560°C, the time is 1-2h; the third stage temperature is 550°C, the time is 1h; the strip heat treatment speed is 32m / min; the coating is a suspension prepared by adding zinc carbonate, manganese carbonate and calcium carbonate to water after mixing in any proportion, the mass concentration is 0.004%, and the dosage is 3L / min.

[0071] Step 8) rolling and packaging; the obtained electronic aluminum foil has a cubic texture of 96% to 99%. After the corrosion treatment, the corrosion foil is bent 56 to 60 times, the tensile strength is 29Mpa, and the 520Vf specific capacitance is 0.900μF / cm2 to 0.925μF / cm2;

[0072] The raw material for high-purity aluminum liquid casting described in step 1) contains the following percentage components:

[0073] (1) Core aluminum liquid composition: Fe = 8ppm, Si = 12ppm, Cu = 12.4ppm, Zn = 1.6ppm, Ti = 2ppm, Mn < 2ppm, other elements < 5ppm, the balance is Al;

[0074] (2) Composition of molten aluminum in the erosion layer: Fe: 17 ppm, Si: 20 ppm, Cu: 55 ppm, Zn = 17 ppm, Mg = 3.4 ppm, Ga = 13 ppm, Pb: 2.2 ppm, and the remainder is Al.

[0075] (3) Ingot casting: Cast in the order of (lower) erosion layer aluminum liquid - core layer aluminum liquid - (upper) erosion layer aluminum liquid. Thickness ratio: The thickness of the upper and lower erosion layer aluminum ingots is consistent, and the thickness ratio of each erosion layer is controlled to be 40%, and the thickness ratio of the core layer aluminum ingot is controlled to be 20%.

[0076] Embodiment 3:

[0077] The present embodiment provides a composite electronic aluminum foil with a thickness controlled to be 135 to 137 microns.

[0078] The core layer has Al>99.99wt.%, which is the tunnel hole termination layer. The content of each element is as follows: Fe=7ppm, Si=14ppm, Cu=12ppm, Zn=1ppm, Ti=3ppm, Mn=3ppm, other elements<5ppm, and the balance is Al; the thickness is 34.0~36.0 microns.

[0079] The erosion layer contains Al>99.985wt.%, which is a tunnel hole growth layer. The content of each element is as follows: Fe: 18ppm, Si: 27.5ppm, Cu: 55ppm, Zn=17ppm, Mg=3ppm, Ga=15ppm, Pb: 2.35ppm, and the balance is Al; the thickness of the upper and lower erosion layers is consistent, and the thickness is controlled to be 49.5-50.5 microns

[0080] The preparation of the composite electronic aluminum foil of this embodiment includes the following steps:

[0081] Step 1) Casting: The raw materials for casting two kinds of high-purity aluminum liquid (core layer aluminum liquid and erosion layer aluminum liquid) are respectively smelted, heat-insulated, refined and left to stand, and then semi-continuously cast to produce ingots at a casting temperature of 675-715° C. and rapidly cooled to obtain formed ingots;

[0082] Step 2) homogenization: the formed flat ingot obtained in the previous step is homogenized in an annealing furnace at a homogenization temperature of 560-590° C. for a homogenization time of 16-24 hours, and then air-cooled to room temperature;

[0083] Step 3) hot rolling: hot rolling the flat ingot after the homogenization treatment in the previous step, with the hot rolling start temperature of 500-550° C. and the final rolling temperature of 260-340° C. to obtain a hot rolled coil with a hot rolling thickness of 5-9 mm;

[0084] Step 4) cold rolling: cold rolling the hot rolled coil obtained in the previous step at a cold rolling speed of 150-300 m / min to obtain a cold rolled coil with an intermediate thickness of 0.16-0.20 mm;

[0085] Step 5) cleaning and intermediate annealing: the cold-rolled coil obtained in the previous step is washed and scrubbed with deionized water containing an alkaline additive, and then rinsed with deionized water, the water temperature is controlled at 70-80°C, the outlet is blown dry with high-pressure air and squeezed with a squeeze roller, and intermediate annealing is performed in a continuous air cushion furnace using a belt type, the annealing temperature is 310-345°C, the annealing speed is 22-36m / min, and the coil is air-cooled to room temperature after annealing;

[0086] Step 6) foil rolling: applying 8-48% deformation by foil rolling, the finished product pass adopts bright rolling with ≤3% reduction, the foil rolling speed is 160-310m / min, and the thickness of the obtained finished product is 0.10-0.15mm;

[0087] Step 7) cleaning and finished product annealing: the cold-rolled coil obtained in the previous step is cleaned with deionized water containing an alkaline additive and then rinsed with deionized water, the water temperature is controlled at 70-80°C, and the outlet is dried with high-pressure air and squeezed with a squeeze roller; during annealing, the coating is evenly sprayed on the coil surface by spraying, and the finished aluminum foil is annealed in a continuous air cushion furnace. The annealing adopts multi-stage annealing at different temperatures, the first stage temperature is 410-450°C, the time is 20min; the second stage temperature is 550-590°C, the time is 1-2h; the third stage temperature is 520-580°C, the time is 1h; the strip heat treatment speed is 25-38m / min; the coating is a suspension prepared by adding zinc carbonate, manganese carbonate and calcium carbonate to water after mixing in any proportion, the mass concentration is 0.001-0.005%, and the dosage is 2-5L / min.

[0088] Step 8) rolling and packaging; the obtained electronic aluminum foil has a cubic texture of 96% to 99%. After the corrosion treatment, the corrosion foil is bent 67 to 70 times, the tensile strength is 35Mpa, and the 520Vf specific capacitance is 0.85μF / cm2 to 0.875μF / cm2;

[0089] The high purity aluminum liquid composition described in step 1) is:

[0090] (1) Core aluminum liquid: Fe 8ppm, Si 10ppm, Cu 12ppm, Zn 1ppm, Ti 3ppm, Mn 3ppm, others <5ppm, the balance is Al;

[0091] (2) Erosion layer aluminum liquid: 18ppm, Si: 27ppm, Cu: 57ppm, Zn 15ppm, Mg 3ppm, Ga 10ppm, Pb: 2.25ppm, the balance is Al.

[0092] (3) Ingot casting: Cast in the order of (lower) erosion layer aluminum liquid - core layer aluminum liquid - (upper) erosion layer aluminum liquid. Thickness ratio: the thickness of the upper and lower erosion layer aluminum ingots is consistent, the control ratio is 36.80-37.50%, and the thickness control ratio of the core layer aluminum ingot is 25.0-26.4%.

[0093] Comparative Example 1:

[0094] Follow these steps to implement:

[0095] Step 1: The segregated primary raw materials and secondary raw materials are cast into high-purity aluminum ingots by semi-continuous casting; the cooling water speed during semi-continuous casting is controlled at 2000-3600L / min; the casting speed is controlled at 42-50mm / min; and the casting temperature is controlled at 680-720℃. The high-purity aluminum ingots produced in this way have uniform structure and few defects such as surface cold shut.

[0096] Step 2: milling the high-purity aluminum ingot, homogenizing annealing, the homogenizing annealing temperature is 540-620° C., the homogenizing annealing time is 20-50 hours, and then cooling, hot rolling at 480-560° C., to obtain the first high-purity aluminum strip.

[0097] When hot rolling the flat ingot, a large reduction rate is adopted to crush the grains and refine the middle structure. The reduction rate of each pass is between 40-70%, and the lattice structure of the entire flat ingot is finally consistent and fine without excessive load affecting the surface quality; under the single-pass high processing rate production, the plate type consistency is ensured, and the hot rolling deformation rate is between 0-90% by using the bending roll control method, the bending roll adopts balanced rolling, the hot rolling deformation rate is between 90-95%, the bending roll adopts negative bending 10-20% rolling, the hot rolling deformation rate is between 95-97%, the bending roll adopts negative bending 20-30% rolling, and when the hot rolling deformation rate is above 97%, the bending roll adopts negative bending 30-50% rolling. After hot rolling, the thickness of the first high-purity aluminum strip is 4-8mm.

[0098] Step three, subjecting the first high-purity aluminum strip to multiple cold rolling processes to obtain a second high-purity aluminum strip, the thickness of the second high-purity aluminum strip is 0.2-0.6 mm, and then foil rolling to obtain a third high-purity aluminum strip.

[0099] Step 4: Add oil to clean the third high-purity aluminum strip, control the cleaning speed at 70-120m / min, ensure that the foil surface is dry, reduce the residue of cleaning agent (oil), place it in a drying oven for drying, and control the temperature of the drying oven at 90-150°C. Then, heat it to 240-270°C in 2-8 hours, and keep it at 240-270°C for 15-30h to achieve the purpose of surface degreasing and intermediate annealing. During the intermediate annealing, air is used as the annealing medium. Then, the finished product is rolled to obtain the first aluminum foil, and the thickness of the first aluminum foil is 0.06-0.200mm.

[0100] Step 5: Cut the first aluminum foil into shear rolls with a width of 450-550 mm and a weight of 200-800 kg.

[0101] The shear coil is subjected to multi-stage annealing. First, the furnace temperature is raised to 250-330°C in 2-6 hours, and kept warm for 3-8 hours. The furnace temperature is then raised to 350-420°C in 3-7 hours and kept warm for 8-15 hours. Subsequently, the furnace temperature is raised to 480-530°C in 2-8 hours and kept warm for 6-12 hours. The furnace temperature is then raised to 580-620°C in 3-6 hours, and kept warm until the temperature of the shear coil reaches 500-540°C. The furnace temperature is then lowered to 500-540°C, and kept warm for 3-10 hours. The finished product is then taken out of the furnace.

[0102] The composition of the finished product is as follows:

[0103] Al≥99.9wt%, Fe: 5-35ppm, Si: 5-35ppm, Cu: 10-100ppm, Pb: 0.2-3ppm, Zn: 2-30ppm, Mn: 2-30ppm, Ga: 2-30ppm, trace elements (one or more of cerium, scandium, zirconium, vanadium, chromium, nickel, magnesium, tin): 3-25ppm.

[0104] Among them, the content of Pb is preferably 2-2.5ppm. The Pb element is enriched in the oxide layer on the surface of the electronic aluminum foil, and plays a role in promoting corrosion during the initial corrosion. When the Pb content is low, the initial corrosion pores are insufficient and the capacity cannot be improved. When the Pb content is too high, there are more corrosion pores, the product is not corrosion-resistant, and the bending strength is reduced. Among them, the content of Zn is preferably 10-20ppm. The Zn element has the effect of promoting the corrosion pores of the electronic aluminum foil, especially affecting the length of the corrosion pores, and has a significant impact on high-thickness electronic aluminum foil products. Secondly, the Zn content has a strong effect on improving the strength of the electronic aluminum foil product and preventing coarse grains. Among them, the content of Mn is preferably 5-10ppm. The Mn element promotes the corrosion pores of the product. The appropriate amount of Mn element can increase the pore size of the corrosion pores and can improve the electrostatic capacity of the electronic aluminum foil product. However, when the Mn content is too high, it is easy to cause corrosion pores, resulting in uneven pores, reduced capacity, and reduced bendability.

[0105] The obtained electronic aluminum foil has a cubic texture of 96% to 98%. After corrosion treatment, the corrosion foil is bent 45 to 53 times, with a tensile strength of 23.5 MPa, a 520 Vf specific capacitance of 0.83 μF / cm2 to 0.845 μF / cm2, and a core layer thickness of 22.0 to 30.0 microns.

[0106] The performance of the above examples and comparative examples is shown in Table 1.

[0107] Table 1 Quality index data of different technical solutions

[0108]

Claims

1. A composite electronic aluminum foil, characterized in that: The electronic aluminum foil is a three-layer composite structure, wherein: the middle layer is a core layer for controlling mechanical properties, and the upper and lower layers are erosion layers that are beneficial to the growth of tunnel holes; the thickness of the electronic aluminum foil is 85 to 150 microns.

2. The composite electronic aluminum foil according to claim 1, characterized in that: The core layer is a tunnel hole termination layer, in which the Al content is greater than 99.99wt.%; the chemical composition of the core layer is: Fe<10ppm, Si<15ppm, Cu<15ppm, Zn<2ppm, Ti<5ppm, Mn<5ppm, the total amount of other elements is <5ppm, and the balance is Al; the core layer thickness is 25 to 35 microns.

3. The composite electronic aluminum foil according to claim 1, characterized in that: The erosion layer is a tunnel hole growth layer, and the Al content in the erosion layer is greater than 99.985wt.%; the chemical composition of the erosion layer is: Fe: 10-20ppm, Si: 5-30ppm, Cu: 50-60ppm, Zn<20ppm, Mg<5ppm, Ga<15ppm, Pb: 2-2.5ppm, and the remainder is Al; the thickness of the upper and lower erosion layers is kept consistent, and the thickness is controlled to be 30-60 microns.

4. The composite electronic aluminum foil according to any one of claims 1 to 3, characterized in that: The cubic texture of the electronic aluminum foil is 96-99%. After the corrosion treatment, the corrosion foil is bent 50-70 times, the tensile strength is 25Mpa-35Mpa, and the specific capacitance is 0.83μF / cm2-0.925μF / cm2.

5. The method for manufacturing a composite electronic aluminum foil according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: (1) Casting: Two kinds of high-purity aluminum liquid are prepared, and after smelting, heat preservation, refining and standing, semi-continuous casting is used to produce flat ingots. The casting temperature is 675-715°C, and the flat ingots are formed by rapid cooling. The two kinds of high-purity aluminum liquid are core layer aluminum liquid and erosion layer aluminum liquid; (2) Homogenization: The formed flat ingot obtained in step (1) is homogenized in an annealing furnace at a temperature of 560 to 590° C. for a time of 16 to 24 h, and then air-cooled to room temperature after homogenization; (3) Hot rolling: The slab after homogenization is hot rolled at a starting temperature of 500 to 550° C. and a final rolling temperature of 260 to 340° C. to obtain a hot rolled coil with a hot rolled thickness of 5 to 9 mm; (4) Cold rolling: cold rolling the hot rolled coil at a speed of 150 to 300 m / min to obtain a cold rolled coil with a thickness of 0.16 to 0.20 mm; (5) Cleaning and intermediate annealing: The obtained cold-rolled coil is washed and scrubbed with deionized water containing alkaline additives in a cleaning device, and then rinsed with deionized water at a water temperature of 70-80°C. After cleaning, the cold-rolled coil is blown dry with high-pressure air and squeezed dry with a squeeze roller at the outlet; then intermediate annealing is performed in a continuous air cushion furnace at an annealing temperature of 310-345°C and an annealing speed of 22-36 m / min. After annealing, the coil is cooled to room temperature by air; (6) Foil rolling: Foil rolling is used to apply a deformation of 8 to 48%, and the finished product is bright rolled with a reduction of ≤3% at a foil rolling speed of 160 to 310 m / min. The thickness of the finished product is 0.10 to 0.15 mm. (7) Cleaning and finished product annealing: the cold-rolled coil obtained in step (6) is cleaned in a cleaning device using deionized water containing an alkaline additive, and then rinsed with deionized water, with the water temperature controlled at 70-80° C. After cleaning, the cold-rolled coil is blown dry with high-pressure air and squeezed dry with a squeeze roller at the outlet of the cold-rolled coil; during annealing, the coating is evenly sprayed onto the coil surface by spraying, and the aluminum foil finished product is annealed in a continuous air cushion furnace, and the electronic aluminum foil is obtained after the finished product annealing; Step 8) Divide into rolls and package.

6. The method for manufacturing composite electronic aluminum foil according to claim 5, characterized in that: In step (1), the chemical composition of the core layer aluminum liquid is controlled as follows: Fe<10ppm, Si<15ppm, Cu<15ppm, Zn<2ppm, Ti<5ppm, Mn<5ppm, other elements<5ppm, and the balance is Al.

7. The method for manufacturing composite electronic aluminum foil according to claim 5, characterized in that: In step (1), the chemical composition of the erosion layer aluminum liquid is controlled as follows: Fe: 10-20ppm, Si: 15-30ppm, Cu: 50-60ppm, Zn<20ppm, Mg<5ppm, Ga<15ppm, Pb: 2-2.5ppm, and the remainder is Al.

8. The method for manufacturing composite electronic aluminum foil according to claim 5, characterized in that: During the ingot preparation process of step (1), the aluminum liquid of the lower erosion layer-the aluminum liquid of the core layer-the aluminum liquid of the upper erosion layer are poured in sequence, and the thickness ratio is: the thickness of the upper and lower erosion layer aluminum ingots is kept consistent, the thickness of the upper erosion layer or the lower erosion layer accounts for 35.0-41.5% of the total thickness of the ingot, and the thickness of the core layer aluminum ingot is controlled to account for 17.0-30.0% of the total thickness of the ingot.

9. The method for manufacturing composite electronic aluminum foil according to claim 5, characterized in that: In step (7), annealing is performed at multiple different temperatures, which are: first stage temperature 410-450°C, second stage temperature 550-590°C, third stage temperature 520-580°C; and the strip heat treatment speed is 25-38 m / min.

10. The method for manufacturing composite electronic aluminum foil according to claim 5, characterized in that: In step (7), the coating is a suspension prepared by mixing zinc carbonate, manganese carbonate and calcium carbonate in any proportion and adding the mixture into water, the mass concentration is 0.001-0.005%, and the dosage is 2-5 L / min.

Citation Information

Patent Citations

  • An electronic aluminum foil composite material and the electronic aluminum foil prepared therefrom

    CN111195657B

  • Production method of aluminium foil used in electrolytic capacitor high voltage anode

    CN1807673B